Dietary Supplements, Resistance Training, and Kidney Stone Risk: A Narrative Review - Miroński, Adam; Minik, Bartosz; Częczek, Kacper; Cieślewicz, Karolina; Szymańska-Zdyb, Kinga; Nowaczek, Patrycja; Braksal, Barbara; Mirkowski, Krzysztof; Szurek, Zuzanna Wanda; Chyła, Zofia Julia (Quality in Sport, 2026)
Background. Dietary supplements are widely used by resistance-trained individuals to support hypertrophy, strength, recovery, and performance. Nephrolithiasis is a recurrent condition influenced by urine volume, urinary pH, calcium, oxalate, uric acid, citrate, sodium intake, and dietary patterns. Aim. The aim of this narrative review was to analyse the potential relationship between common gym supplements and risk factors for kidney stone formation. Material and methods. A narrative literature review was conducted using PubMed, Scopus, Web of Science, ScienceDirect, Google Scholar, urological guidelines, and sports nutrition position statements. The synthesis focused on protein supplements, creatine, vitamin C, calcium, vitamin D, caffeine-containing pre-workout products, hydration, and dietary context. Results. The main concerns relate to high-dose vitamin C, excessive non-dairy animal protein intake, high sodium intake, low urine volume, and poorly supervised calcium or vitamin D supplementation in predisposed individuals. Recommended-dose creatine is not convincingly linked with nephrolithiasis in healthy users. Conclusions. Supplement use should be interpreted within total diet, hydration, training conditions, and individual stone risk. Prevention includes adequate fluid intake, moderate protein intake, sodium restriction, sufficient dietary calcium, avoidance of excessive vitamin C, and medical evaluation in recurrent stone formers. Keywords: resistance training, dietary supplements, nephrolithiasis, kidney stones, protein supplements, creatine, vitamin C, hydration